Methods of or the dissemination of food processing technologies: the soybean example in Nigeria - Osho, S.M. (International Society for Horticultural Science, 1994)
Protein deficiency is still a major problem in Nigeria and in Africa, particularly among the low-income groups. Cassava is the staple food for millions of people in Africa. Soybean could be fortified with cassava to reduce the alleviation of malnutrition problems caused by root crop based Nigerian/African diets. The IDRC Soybean Utilization Project, jointly implemented by IITA and national institutes in Nigeria, has been successful in developing several different uses for soybean in foods and disseminating this technology to rural and urban people. This was found to have increased the production and utilization of soybean in Nigeria. The processes and technology developed during the project helped to overcome the technological constraints of promoting soybean use and to make it a common protein food in Nigeria. This can be used as a model for disseminating technologies developed on cassava.